Dictionary form in decoding, encoding and retention: Further insights. Issue 3 (6th June 2017) - Dziemianko, Anna
Abstract: The aim of the paper is to investigate the role of dictionary form (paper versus electronic) in language reception, production and retention. The body of existing research does not give a clear answer as to which dictionary medium benefits users more. Divergent findings from many studies into the topic might stem from differences in research methodology (including the various tasks, participants and dictionaries used by different authors). Even a series of studies conducted by one researcher (Dziemianko, 2010, 2011, 2012b) leads to contradictory conclusions, possibly because of the use of paper and electronic versions of existing dictionaries, and the resulting problem with isolating dictionary form as a factor. To be able to argue with confidence that the results obtained follow from different dictionary formats, rather than presentation issues, research methodology should be improved. To successfully generalize about the significance of the medium for decoding, encoding and learning, the current study replicates previous research, but the presentation of lexicographic data on paper and on screen is now balanced, and the paper/electronic opposition is operationalized more appropriately. A real online dictionary and its paper-based counterpart composed of printouts of screen displays were used in the experiment in which the meaning of English nouns and phrases was explained, and collocations were completed with missing prepositions. A delayed post-test checked the retention of the meanings and collocations. The results indicate that dictionary medium does not play a statistically significant role in reception and production, but it considerably affects retention.